ChemInform Abstract: Studies on the Biginelli Reactions of Salicylaldehyde and 2‐Hydroxy‐1‐naphthaldehyde. Issue 47 (6th November 2014) - Liu, Qingjian; Xu, Jiehua; Teng, Fei; Chen, Anjun; Pan, Ning; Zhang, Wenwen
Abstract Chemoselectivity of the Biginelli Reactions depends on the reaction conditions used, tricyclic bridged pyrimidine derivatives are formed upon refluxing whereas, at lower temperatures pyrimidine derivatives of type (IV) are formed.